Assimilation between Bond Market and Stock Market (Global Journal of Management and Business Research, 2012)
The research work deals with studying of the relation between shares and bonds and comparative analysis of stock (shares) which are listed on stock market exchange and bonds (Government Securities) which are listed in NSE Government security index, which issued in whole sale debt market. For evaluating the relation between stock and bond market to study the comparative analyses of both markets and also finds out the correlation and cointegration between both markets, whether these markets correct each other or not. The objective of this paper is to scrutinize the correlation and linkage structure of stock and bond return across different time-phase horizon between stock and Bond Market Indices over a period from January 2005 to Dec 2010. The findings outbuilding some light on the presence of mean deteriorating arrangement of correlation across changed economic environments. During the economic richness, there is an indication of positive and significant correlation between bond and stock returns. An insignificant positive correlation was also observed during the recession period. Conversely, in the course of the recovery period, negative and insignificant relation was observed. Conclusions on co-movement of stock and bond index recommend no evenness relationship with any short-term error correction. Results also indicate that the stock and bond markets of are independent of each other, with most of the variations in indices being explained by past value of each respective market Indian capital market.
Keywords: Bond Index; Stock Index